Applying green gamification to support green campus initiatives in reducing carbon emissions / Romiza Md Nor and Nur Alyaa Azhar - Md Nor, Romiza; Azhar, Nur Alyaa (UiTM Cawangan Perlis, 2017)
Green gamification is a technique with the purpose of using game elements in non-game context to encourage positive environmental behaviours. It is believe to be able to support behaviour change with the help of persuasive technology which is the Go Green Campus web application. The objective of this project is to create awareness on environment sustainability by applying green gamification technique to encourage behaviour change in reducing carbon emissions which is believed to be more fun and enjoyable. This research focuses on the college students in UiTM Perlis as an initiative to Green Campus concept. The research significance is to motivate people to change their behaviour in order to reduce carbon emission. Evaluation of the web application has been conducted using heuristic evaluation which consists of three elements: perceived, structural and perceptual elements. Questionnaires were distributed among ten college students where they had been closely monitored by researchers for two weeks. The results show that besides feeling motivated to realize that each activity can contribute to reducing carbon emission, almost all participants enjoyed the green gamification elements since they are enjoyable and fun.